2009
DOI: 10.1177/145507250902600404
|View full text |Cite
|
Sign up to set email alerts
|

What is the Worst Thing you could get Hooked on?: Popular Images of Addiction Problems in Contemporary Sweden

Abstract: Aims To investigate potentially crucial aspects of Swedes' perceptions of nine different addictions. Data and Methods Population survey, sent out to 2,000 adult Swedes (18–74 years), focusing on the perceived severity of, responsibility for, options to recover from, and character of addiction to cigarettes, snuff, alcohol, cannabis, amphetamine, cocaine, heroin, medical drugs, and gambling. Results There are large differences in the ways in which various addiction problems are perceived. Whereas tobacco use, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 19 publications
7
60
1
2
Order By: Relevance
“…Profession, gender and education produced some differences. The results resembled those of the similar general population survey in Sweden, indicating that the risks of familiar addictions are downplayed, whereas the risks of uncommon addictive behaviors are overstated (Blomqvist, 2009;Blomqvist, Koski-Jännes, & Cunningham, 2014).…”
Section: Theoretical Underpinnings and Previous Researchsupporting
confidence: 70%
See 1 more Smart Citation
“…Profession, gender and education produced some differences. The results resembled those of the similar general population survey in Sweden, indicating that the risks of familiar addictions are downplayed, whereas the risks of uncommon addictive behaviors are overstated (Blomqvist, 2009;Blomqvist, Koski-Jännes, & Cunningham, 2014).…”
Section: Theoretical Underpinnings and Previous Researchsupporting
confidence: 70%
“…The questionnaire used for this study was originally developed by Jan Blomqvist (2009) in Sweden. The translation of the questions was conducted and double checked with due care, first for a comparative general population survey and then for this survey.…”
Section: Questionnaires and Data Collectionmentioning
confidence: 99%
“…Although the "Brickman models" have been found to be useful in exploring how addictions are conceptualized in various contexts (e.g. Blomqvist, 1998Blomqvist, , 2009Edman and Blomqvist, 2011;Koski-Jä nnes et al, 2012a), previous studies have also pointed to certain ambiguities. Thus, it is evident that various ways of operationalizing the models will give differing results as concerns the overall support for a certain model, which means that the models are perhaps most useful in comparative studies.…”
Section: Conceptions Of Addiction and Recoverymentioning
confidence: 99%
“…Blomqvist, 2004), as opposed to a rather strong public opinion in Canada in favour of legalizing cannabis (Kennedy, 2012). As concerns addiction to cigarettes, previous analyses have shown that Swedes tend to regard smoking less as an addiction than as a "bad habit", for which the individual is personally responsible, and which s/he is principally able to quit (Blomqvist, 2009(Blomqvist, , 2012. Possibly Canadians are, perhaps due to larger media attention, and a stronger influence from the American "disease" notion of addiction, and the Surgeon General's (The Reports of the Surgeon General, 1988) description of smoking as an expression of "nicotine dependence", more inclined to see smoking as a problem, for which society should take responsibility.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation